Measuring the Concentration of Plasma "Lipid Profile and Iron" in Al-Mustaqbal University College Smokers - Hasan, Qusay Azeez; Jawad, Sabrean; Ibadi, Emam; Abdulla, Aliaa Kareem; Zigam, Qassim A.; Hasan Owadh, Hasanain Kamil (Journal of Biomedicine and Biochemistry, 2023)
In developed countries, the biggest factor leading to death is cigarette smok- ing, where smoking causes cancers, congestive heart diseases, pulmonary diseases, and other diseases. This study was conducted at Al-Mustaqbal University College - Hilla - Iraq, to evaluate the effect of smoking types on lipid profile (triglycerides, cholesterol, low-density lipoproteins (LDL), very low-density lipoprotein (VLDL), high-density lipoprotein (HDL), and iron. The study included 24 samples of males and the study targeted three groups: the control group (group 1= 7) without smoking, regular cigarette R.C (group 2= 8) smokers of regular cigarettes, and the last group 3 (elec- tron cigarette E.C) comprised of 9 samples (people who smoke electronic cigarettes). The samples studied were of a similar age group ranging from 19 to 30 years. The levels of triglycerides and cholesterol were observed to increase in group 2 compared to the control group. The level of HDL increased in group R.C. by comparing it with the control group, while the iron level increased in group E.C. in comparison to both the groups (control and R.C).The results showed that the use of electronic cigarettes E.C. was less severe than regular cigarettes R.C., while both had high marks compared to the control group.